High Serum SHBG Predicts Incident Vertebral Fractures in Elderly Men. (20th January 2016) - Vandenput, Liesbeth; Mellström, Dan; Kindmark, Andreas; Johansson, Helena; Lorentzon, Mattias; Leung, Jason; Redlund‐Johnell, Inga; Rosengren, Björn E; Karlsson, Magnus K; Wang, Yi‐Xiang; Kwok, Timothy; Ohlsson, Claes
ABSTRACT: Previous prospective cohort studies have shown that serum levels of sex steroids and sex hormone‐binding globulin (SHBG) associate with nonvertebral fracture risk in men. The predictive value of sex hormones and SHBG for vertebral fracture risk specifically is, however, less studied. Elderly men (aged ≥65 years) from Sweden and Hong Kong participating in the Osteoporotic Fractures in Men (MrOS) study had baseline estradiol and testosterone analyzed by gas chromatography–mass spectrometry (GC‐MS) and SHBG by immunoradiometric assay (IRMA). Incident clinical vertebral fractures ( n = 242 cases) were evaluated in 4324 men during an average follow‐up of 9.1 years. In a subsample of these men ( n = 2256), spine X‐rays were obtained at baseline and after an average follow‐up of 4.3 years to identify incident radiographic vertebral fractures ( n = 157 cases). The likelihood of incident clinical and radiographic vertebral fractures was estimated by Cox proportional hazards models and logistic regression models, respectively. Neither serum estradiol (hazard ratio [HR] per SD increase = 0.93, 95% confidence interval [CI] 0.80–1.08) nor testosterone (1.05, 0.91–1.21) predicted incident clinical vertebral fractures in age‐adjusted models in the combined data set. High serum SHBG, however, associated with increased clinical vertebral fracture risk (1.24, 1.12–1.37). This association remained significant after further adjustment for FRAX with or without bone mineral density (BMD). SHBG also associated with increased incident radiographic vertebral fracture risk (combined data set; odds ratio [OR] per SD increase = 1.23, 95% CI 1.05–1.44). This association remained significant after adjustment for FRAX with or without BMD. In conclusion, high SHBG predicts incident clinical and radiographic vertebral fractures in elderly men and adds moderate information beyond FRAX with BMD for vertebral fracture risk prediction. © 2015 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.